IMPLEMENTASI NILAI-NILAI PANCASILA DALAM HUKUM EKONOMI UNTUK MEWUJUDKAN KEADILAN SOSIAL DAN PERTUMBUHAN EKONOMI - Alif Lukmanul Hakim; Al-Amin (Prosiding Seminar Nasional Indonesia, 2025)
This study aims to analyse the implementation of Pancasila values in Indonesia's economic legal system as an effort to achieve social justice and sustainable economic growth. Using a literature review method, this study examines various literature, regulations, and policies related to the application of Pancasila principles, particularly in the context of a people-centred economy, equitable distribution of development outcomes, and protection of small and medium-sized enterprises. The analysis reveals that Pancasila values, such as mutual cooperation, solidarity, and social justice, have become the normative foundation for the formulation of national economic law. However, structural challenges in the era of globalisation, such as the dominance of capitalism, resource distribution disparities, and foreign investment penetration, still hinder the optimal realisation of these values. Therefore, regulatory reforms, institutional strengthening, and the internalisation of Pancasila values in education and economic practices are necessary to create an inclusive, fair, and competitive economic legal system.